A retextualização como estratégia para o ensino de produção textual.: de textos da mídia a contos policiais - Roberta Garcia (2015)
It is of great concern that many students begin the 6th year and to continue the elementary school, reaching the 9th grade without developing skills in writing provided in official educational documents such as the Common Basic Contents of Minas Gerais (BCC / MG) . This problem points to the need for changes in the practice of teaching of Portuguese, which traditionally opens little room to work with issues related to the systematization of the writing and rewriting school. However, it is possible to conduct diverse pedagogical practices in an innovative environment, dealing with various themes, creatively, and taking into account the daily lives of students, their previous knowledge, their interests and their curricular needs. The advent of studies in Linguistics, Sociolinguistics and Psycholinguistics about reading and writing teaching brought significant contributions, from a theoretical point of view. Scholars such as Bakhtin (1992), Koch (2002), Dolz and Schneuwly (2004), Marcuschi (2006), among others, present theories in which are embedded the idea of texts as social events, in which the subjects are seen as protagonists agents in their productions and textual analysis .. From perspective, the texts begin to form themselves into social activities and no longer an instrument to verify the knowledge of grammatical rules. In this light, one should take into account the sociocomunicativa, historical and cultural situation to work with texts. It is in the context of these theories and propositions about the teaching of reading and writing than that of the project presented here. Our main goal is to enable students to nine, from 6th to 9th year of a municipal school in Brumadinho / MG, a greater insertion in literate practices and a more critical view regarding the media discourse on crime. This issue will be worked by a literary bias, in that it will be analyzed and elaborated detective stories. Thus, we seek to establish a relationship between theory and practice. The methodology of this research brings the possibility of analyzing the social situation in which they live students involved in the project and its relationship to learning the language. Therefore, it appears as an action research, qualitative, since it will be not made a quantitative assessment, but reflective about the process of learning, throughout your application. For the implementation of the proposed seven workshops were prepared, with activities that include analytical work of television programs and music, reading, retextualization of media texts to detective stories and rewrite, which will allow students an approach to the subject of interest and a systematic and planned learning process in relation to the text production and reading. Thus, it is expected to contribute to the social and educational integration of these students, encouraging their learning, the recovery of confidence in their potential, and expanding its possibilities for citizen participation.